Monolayer molecular probes for detection of trace amounts of cyanide anions. Issue 128 (14th December 2015) - Wu, Fei; Zhao, Shangbi; Zhu, Linna
Abstract : A monolayer sensor M-P1 is developed for detection of cyanide ions in aqueous solution. The monolayer sensor has high sensitivity and selectivity, and is very efficient for detecting trace amounts of analytes in dilute solution. Abstract : In this work, monolayer sensor molecules are firstly developed for the detection of trace amounts of cyanide ions in aqueous solution, which was inspired by the fact that in dye-sensitized solar cells, dye molecules adsorb onto the semiconductor surface by forming a monolayer. Compound P1 is a well-known p-type dye molecule in dye-sensitized solar cells, with a carboxyl group on the triphenylamine used as the anchoring point. Thus it could be adsorbed onto a metal oxide (such as TiO2 and NiO) surface to form a monolayer M-P1. M-P1 detects cyanide through a nucleophilic addition reaction between the negatively charged CN − and the dicyanovinyl group, resulting in a weaker intramolecular charge transfer from the donor to acceptor in P1. The detection behavior could be easily observed from a visual color change of the metal oxide films, which was also in agreement with their UV-vis absorption spectral changes. Since the adsorbed sensor molecules are in very small amounts (at the nM level), M-P1 could be applied to detect trace amounts of CN − in aqueous solution (pH = 7.4) with high sensitivity, selectivity and anti-interference ability. The detection limit of the monolayer sensor is determined to be 2.99 nM, which is far below the WHO cyanide standard for drinking water (1.9 μM). Additionally, it is much lower than that obtained by dissolving P1 and the analytes in organic solution. The results demonstrate that the monolayer sensor has high sensitivity and selectivity, and is very efficient for detecting trace amounts of analytes in dilute solution, and the detection could be easily observed by the naked eye. Moreover, the idea of a monolayer sensor excludes the requirement of an organic environment for reaction-based sensors to function, and provides new possibilities for constructing probes in the future.